Bioanalysis of antihistamines for clinical or forensic purposes. (10th June 2016) - Katselou, Maria; Papoutsis, Ioannis; Nikolaou, Panagiota; Spiliopoulou, Chara; Athanaselis, Sotiris
Abstract: Antihistamines are a class of drugs that inhibit the action of histamine and are used to alleviate symptoms associated with allergic reactions, but some of them can cause side effects, the most unpleasant and dangerous of which are the sedative effects that may hinder important psychological functions and impair skilled performance. These side effects could decrease safety in certain common and critical tasks, such as driving or operating machinery, leading to accidents. Antihistamines can also cause intoxications, sometimes lethal, especially when co‐administered with alcohol or other sedative drugs. Thus, the development of analytical methods for their determination in biological fluids is considered to be useful for the investigation of clinical and forensic cases. These methodologies could also be used for pharmacokinetic studies. Several liquid and a few gas chromatographic methods have been developed for the determination of antihistamines in biological matrices after proper pretreatment procedures. This article reviews the published analytical methodologies that were gathered through the search in PubMed database and the recent developments on isolation or determination of antihistamines in biological materials. Current trends and future perspectives on bioanalysis of antihistamines are also discussed. Copyright © 2016 John Wiley & Sons, Ltd.